Comparison of Physical Fitness and Cardiopulmonary Exercise Test Performance Using Arm Versus Leg Cycling in Patients With Cardiovascular or Pulmonary Disease–A Systematic Review and Meta-analysis. Issue 4 (October 2018) - Tolstrup Larsen, Rasmus; Hermann Tang, Lars; Keller, Camilla; Christensen, Jan; Taylor, Rod S.; Doherty, Patrick; Langberg, Henning; Zwisler, Ann-Dorthe
Abstract : Purpose: Alternative modes of cardiopulmonary exercise testing are needed and an arm cycle (AC) is a promising alternative to the gold standard of the leg cycle (LC). The aim of this study was to undertake a systematic review comparing maximal oxygen consumption (VO2max ) obtained from AC and LC in patient populations with cardiovascular disease (CVD) and pulmonary disease (PD). Methods: A systematic review was undertaken with literature searches on December 5, 2016. Studies were included if they directly compared aerobic capacity values obtained from AC and LC in patients with CVD or PD. Results across studies were pooled using random effects meta-analysis and univariate meta-regression were used to assess potential associations between variables. Results: A total of 14 studies in 411 patients were included. On average, VO2max of LC exceeded AC mean difference by 3.48 mL·kg −1 ·min −1, (95% confidence interval [CI]: 1.94, 5.03) and a mean AC/LC ratio of 0.83, (95% CI: 0.77, 0.90). VO2max differences between AC and LC were similar in patients with CVD compared with PD but were found to be higher in older individuals and those with higher VO2max . Conclusions: Although AC offers an important alternative form of exercise testing for patients with CVD or PD, clinicians must take into account that VO2max values obtained from AC are consistently lower than those obtained on LC. However, the results of this article offer an evidence-based estimation for the proportional differences between AC values and LC values for groups with CVD or groups with PD. Abstract : Supplemental Digital Content is Available in the Text.